Hymenolepiasis in Rats (Rattus Norvegicus) With Its Zoonotic Potential in Mymensingh District of Bangladesh - Singh, Rahul Pratap; Roy, Babul Chandra; Debnath, Asish Kumer; Nahar, Sultana Fizun; Talukder, Md Hasanuzzaman (Research in Agriculture Livestock and Fisheries, 2020)
Hymenolepis nana and Hymenolepis diminuta are globally widespread zoonotic cestodes and rats act as main reservoir host of these cestodes. Wild brown rats (Rattus norvegicus) are the most common rats usually live in human’s dwellings, especially in areas of low socioeconomic status and low levels of hygiene practices. Since there is scarcity of information of the hymenolepiasis in rats in Bangladesh, therefore the aim of this study was to determine the incidence of H. nana and H. diminuta in wild and laboratory rats. A total of 60 rats were collected from the residential areas of rural villages of Mymensingh sadar and the Bangladesh Agricultural University campus and 10 were from the laboratory of the Department of Parasitology, BAU, Mymensingh. The rats were killed by cardiac puncture and tapeworms were collected and subsequently were subjected for morphological study under the stereomicroscope. Two species of cestodes, namely H. nana and H. diminuta were detected showing the overall prevalence of 23.3 % and 35 % respectively. The high prevalence of H. nana (30%) was determined in rats captured from the rural village areas whereas H. diminuta was found more prevalent (60%) in the laboratory rats. The result of the current study suggests that H. nana infection in rural village areas may act as a risk factor for the zoonotic transmission of hymenolepiasis to human in Bangladesh. Res. Agric., Livest. Fish.7(2): 255-259, August 2020